Infant Hand Preference and the Development of Cognitive Abilities - Michel, George F.; Campbell, Julie M.; Marcinowski, Emily C.; Nelson, Eliza L.; Babik, Iryna (Frontiers in Psychology, 2016)
Hand preference develops in the first two postnatal years with nearly half of infants exhibiting a consistent early preference for acquiring objects. Others exhibit a more variable developmental trajectory but by the end of their second postnatal year, most exhibit a consistent hand preference for role-differentiated bimanual manipulation. According to some forms of embodiment theory, these differences in hand use patterns should influence the way children interact with their environments, which, in turn, should affect the structure and function of brain development. Such early differences in brain development should result in different trajectories of psychological development. We present evidence that children with consistent early hand preferences exhibit advanced patterns of cognitive development as compared to children who develop a hand preference later. Differences in the developmental trajectory of hand preference are predictive of developmental differences in language, object management skills, and tool-use skills. As predicted by Cassasanto’s body-specificity hypothesis, infants with different hand preferences proceed along different developmental pathways of cognitive functioning.